Implementation of Restorative Justice in the Settlement of Juvenile Assault Offenses as Street Crimes at the Banda Aceh City Police - Nabilla, Rafika; Sulaiman, Badri Hasan; Mustaqim, Riza Afrian; M. Yunus, Fakhrurrazi (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2026)
Restorative justice is an approach to resolving legal cases that involves the offender and the victim in order to achieve a fair settlement by emphasizing the fulfillment of the rights and obligations of the parties based on humanitarian aspects and more dignified and just legal protection. The implementation of restorative justice in this study is carried out in cases of assault committed by children as perpetrators of street crime at the Banda Aceh Police Resort (Polresta Banda Aceh), focusing on the resolution process of several cases between 2023 to 2025. This study aims to examine how restorative justice is implemented in handling cases of child-perpetrated assault as street crime at Polresta Banda Aceh and to identify the obstacles faced in its effectiveness. This study employs a juridical empirical method with statute approach and conceptual approach. Data are collected through interviews with responsible parties at Polresta Banda Aceh and are analyzed descriptively to provide a detailed overview of the implementation of regulations in practice.The findings indicate that Polresta Banda Aceh has attempted to implement restorative justice through penal mediation involving the offender, the victim, and other related parties. However, not all cases are successfully resolved as expected. Out of 9 cases handled, only 3 cases are successfully resolved through restorative justice, while 6 cases are referred to formal judicial proceedings. The implementation still faces several obstacles, including limited family support, the failure to reach an agreement between the offender and the victim, and the lack of optimal support from customary institutions for children. Although the procedures have been carried out in accordance with existing regulations, this condition indicates a gap between legal norms that require diversion and their implementation in practice. Therefore, it is necessary to enhance the capacity of law enforcement officers through specialized training, accompanied by public education, as well as integrating customary law values, in order to ensure that restorative justice is implemented more effectively.